Factors Affecting Marital Maintenance Behaviors in Economic Pressure from Married Women’s Perspective - Nasim Sheikhi-Fini; Hosein Salimi-Bajestani; Ebrahim Naeimi (Iranian Evolutionary Educational Psychology Journal, 2021)
The current study intended to identify the factors influencing marital maintenance behaviors in economic pressure periods from married women’s perspective. In so doing, a qualitative approach and a phenomenological research methodology was employed. The participants included 15 married women living in Bandar Abbas who were selected through purposive sampling method. The data were collected through semi-structured interviews and were analyzed using Thematic Analysis (TA) technique. The results revealed that the behaviors that maintain the couple's relationship included a main theme, i.e. the behaviors that maintain the couple's relationship. Sub-themes of factors related to couple maintenance behaviors included managing economic conditions, counseling and psychological services, main and core family interaction, and life skills. These findings can be used in the field of divorce prevention and family strengthening.